St Peter of Osor (Island of Cres) and Benedictine monasticism in the Adriatic area - Bully, Sébastien 1969-; Čaušević, Morana; Gioanni, Stéphane 1971- (Rome École française de Rome, 2024)
"This book gathers the proceedings of the international round-table Saint-Pierre d'Osor et le monachisme bénédictin dans l'espace adriatique held in 2018 at Osor on the island of Cres (Croatia), which marked the culmination of twelve archaeological campaigns (2006-2017). The aim of this meeting was to present and contextualise, on a broad geographical and chronological scale, our knowledge of the monastery of St Peter and Benedictine monasticism in the Adriatic, whose importance in the reform of the Church in the 11th century was magnified by the Camaldolese Annals in the 18th century. This multi-disciplinary study of St Peter of Osor and its representations allows us to compare the available sources (archaeological, literary and archival) and to renew our understanding of the island monastery, its presumed foundation by Gaudentius, bishop of Osor and then monk at the Porto Novo monastery in Ancona, and its role in the implementation of the reform. It also sheds new light on Benedictine expansion, the spread of monastic culture, artistic transfers, the movement of people and networks of sociability between the shores of the Adriatic. Finally, it examines the dialogue between archaeology and history." -- Publisher's website
Proceedings of a meeting
Contributions and abstracts in English and Italian
Keywords: Benedictines -- Croatia -- Congresses; Benedictine monasteries -- Croatia -- Congresses; Archaeology, Medieval -- Croatia -- Adriatic Coast -- Congresses; Archéologie médiévale - Croatie - Adriatique, Côte de l'; Conference papers and proceedings; proceedings (reports); Actes de congrès; Osor (Croatia) -- Antiquities -- Congresses; Konferenzschrift